2017
DOI: 10.1002/open.201700055
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Activity of a c‐Type Cytochrome b5 in the Non‐Native State is Comparable to that of Native Peroxidases

Abstract: The design of artificial metalloenzymes has achieved tremendous progress, although few designs can achieve catalytic performances comparable to that of native enzymes. Moreover, the structure and function of artificial metalloenzymes in non‐native states has rarely been explored. Herein, we found that a c‐type cytochrome b 5 (Cyt b 5), N57C/S71C Cyt b 5, with heme covalently attached to the protein matrix through two Cys–heme linkages, adopts a non‐native state with an open heme site after guanidine hydrochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Moreover, both Th 4+ and UO 2 2+ ions reduce the oxy-form of Hb at a high concentration of >100 µM [40]. Cyt b 5 is a small membrane binding heme protein, and its heme-binding domain is highly negatively charged by a series of acidic residues, forming an "acidic" cluster [41][42][43]. Spectroscopic study showed that uranyl may bind to the surface of Cyt b 5 with a binding affinity of K D = 10 µM, and molecular modeling study suggested a possible uranyl binding site at surface residues, Glu37 and Glu43 (Figure 2a) [44,45].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…Moreover, both Th 4+ and UO 2 2+ ions reduce the oxy-form of Hb at a high concentration of >100 µM [40]. Cyt b 5 is a small membrane binding heme protein, and its heme-binding domain is highly negatively charged by a series of acidic residues, forming an "acidic" cluster [41][42][43]. Spectroscopic study showed that uranyl may bind to the surface of Cyt b 5 with a binding affinity of K D = 10 µM, and molecular modeling study suggested a possible uranyl binding site at surface residues, Glu37 and Glu43 (Figure 2a) [44,45].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…4 To increase the protein stability, especially for the heme-binding affinity of heme proteins, a common approach is to construct a covalent heme to protein cross-link, as occurred in natural cytochrome c (Cyt c) and some Cyt P450s. [28][29][30] For example, a Cyt c-like covalent link (Cys-heme cross-link) has been constructed in Cyt b 5 , [31][32][33] Cyt b 562 , 34 ascorbate peroxidase, 35 and myoglobin (Mb). 36 Moreover, other heme-protein cross-links such as Met-Heme, 37 His-Heme, 38 and Tyr-heme, 39,40 can also be designed in articial heme proteins.…”
Section: Introductionmentioning
confidence: 99%